The effect of new silvicultural trends on mental workload of harvester operators - Spinelli, Raffaele (Array, 2020)
Close-to-nature (CTN) forestry offers many advantages, but makes management more complex and generally results in lower harvesting productivity and higher harvesting cost. While the higher harvesting cost of CTN is widely acknowledged, few ever consider the potential impact on operator workload, as the harvesting task becomes more complex. This study aimed to determine the mental workload of harvester operators under two silvicultural regimes: »pure conifer« stand and »mixwood« stand. In total, 13 harvester operators with varying experience levels were monitored for work performance and mental workload when operating a harvester simulator in two virtual stands designed according to the above-mentioned silvicultural regimes. Mental workload was assessed using the NASA Task Load Index (NASA-TLX) interview method and heart rate variability measurements, during two 30-minute test sessions performed in the »pure conifer« and the »mixwood« stand, respectively. As expected, operating in a more diversified »mixwood« stand resulted in a marked productivity loss, estimated between 40 and 57%. The study also confirmed the increased aggravation of mental demand, effort and frustration experienced by the operators when passing from the »pure conifer« stand to the »mixwood« stand. Such increase in mental workload was independent of the age and experience of the operators. Results can be used to paint a more holistic picture of CTN forestry and its implications for harvester operators. Besides increasing the number of subjects being monitored, future studies should focus on live forest operations.